Internalization of Worship Discipline Through the Tahfiz Program at SD Muhammadiyah 2 Sorong - Saputra, Alga Amas; Rasyid, Muhammad Rusdi; Sudrimo, Sella Nofriska (Ta'dib, 2026)
This study aims to analyze the role of the tahfiz program at SD Muhammadiyah 2 Kota Sorong in fostering students’ worship discipline from the perspective of Imam Al-Ghazali. Specifically, it examines the processes of habituation and supervision, identifies the impact on students’ behavioral transformation, and explores challenges in sustaining discipline between school and home environments. This research employs a qualitative approach with a descriptive design. Data were collected through observation, in-depth interviews with teachers, the principal, and Grade V students, as well as documentation of learning and worship activities. The data were analyzed using thematic analysis, including data reduction, coding, categorization, and interpretation to identify key patterns. The findings reveal that the tahfiz program functions as an integrated system combining structured memorization, habituation of religious practices, and continuous supervision. Habituation is implemented through routine worship activities, while supervision is reinforced through monitoring tools such as memorization cards and prayer control books. These processes significantly contribute to students’ behavioral transformation, as reflected in improved punctuality, consistency, motivation, and self-awareness in performing daily prayers. However, the study also identifies challenges in sustaining worship discipline, particularly due to the discontinuity between school and home environments, limited parental involvement, and inconsistent supervision outside school. In conclusion, the tahfiz program effectively supports the internalization of worship discipline when it integrates knowledge, practice, and supervision. However, its sustainability depends on the alignment between school and family environments. Strengthening collaboration between teachers and parents is essential to ensure consistent character development beyond the school context.